Evaluation and fitting of non-conformities of an environmental analysis laboratory towards ISO/IEC 17025:2017: An action research (Research, Society and Development, 2022)
Due to the requirements of customers and/or regulatory bodies, for a laboratory to remain competitive in the market, it must demonstrate technical competence. The implementation and subsequent accreditation/recognition of a quality management system based on ISO/IEC 17025 are capable of ensuring the validity of the results of a testing or calibration laboratory. Therefore, the objective of this work is to identify and propose corrective actions for the nonconformities detected in an environmental analysis laboratory under ISO/IEC 17025:2017. In the period from August to November 2018, the study of the 2005 and 2017 versions of the standard was carried out, an initial internal audit was performed in the laboratory, the causes of nonconformities were identified, an action plan was elaborated and, finally, the results of the actions were evaluated. It were detected 21 nonconformities and proposed 35 corrective actions. Nine actions were satisfactorily concluded. The difficulty to solve problems is due to the lack of equipment and the prioritization of human and financial resources. This research was important for team integration and knowledge sharing in the workplace.